2021
DOI: 10.1016/j.jhin.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Decontaminating N95 respirators during the COVID-19 pandemic: simple and practical approaches to increase decontamination capacity, speed, safety and ease of use

Abstract: Background The COVID-19 pandemic has caused a severe shortage of personal protective equipment (PPE), especially N95 respirators. Efficient, effective and economically feasible methods for large-scale PPE decontamination are urgently needed. Aims (1) to develop protocols for effectively decontaminating PPE using vaporized hydrogen peroxide (VHP); (2) to develop novel approaches that decrease set up and take down time while also increasing decontamination capacity (3) to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
2
11
0
2
Order By: Relevance
“…A systematic review concluded they were unable to draw conclusions on the most efficacious and safe methods for decontaminating surgical masks due to the heterogeneous methods used in studies [ 11 ]. Although the technology that appears to offer the best prospects for decontamination of PPE is hydrogen peroxide vapour [ 12 , 13 ], we strongly support the opinion of Alt et al. that this is an area that should be further explored and developed so that institutions can not only turn to effective decontamination methods that are accessible to them, but can also develop operational plans addressing matters such as user acceptance, traceability and stock management [ 14 ].…”
supporting
confidence: 53%
“…A systematic review concluded they were unable to draw conclusions on the most efficacious and safe methods for decontaminating surgical masks due to the heterogeneous methods used in studies [ 11 ]. Although the technology that appears to offer the best prospects for decontamination of PPE is hydrogen peroxide vapour [ 12 , 13 ], we strongly support the opinion of Alt et al. that this is an area that should be further explored and developed so that institutions can not only turn to effective decontamination methods that are accessible to them, but can also develop operational plans addressing matters such as user acceptance, traceability and stock management [ 14 ].…”
supporting
confidence: 53%
“…In the real-world application, our experience and that of others shows that individual N95 respirators will likely be placed in steam sterilization pouches, paper bags or other containers before being placed in the warming cabinets 13 , 14 . To mimic this, a temperature/RH logger was placed inside several types of bags in order to ascertain that a N95 respirator in a bag or bags in a warming cabinet would be exposed to the appropriate temperature-humidity profile.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of SUP filtering-face piece respirators face masks varies based on type and certification that is defined across three levels of protection depending upon leakage of particles into the interior of the mask that are 22% (FFP1, such as medical and procedural masks), and 8% (FFP2, such as N95-type respirators) and 2% for non-disposable FFP3-type respirators [ 2 ]. Use of non-thermal biocidal and disinfection approaches, such as vaporized hydrogen peroxide (30 to 35% VH2O2) and moist heat (60 to 65°C for 30 min), and ultraviolet light at 254 nm (or fluence at 2000 mJ/cm 2 ), has been applied for reprocessing of FFP1 and FFP2 type respirators, such as under EUA [ 2 , 25 , 26 , 27 ]. Non-thermal disinfection approaches of FFPs have been selected to enable retention of filtration performance, material compatibility, comfort fit and pressure drop.…”
Section: Coronaviruses and Implications For Meeting Personal And Protective Equipment Supply Chain Shortage And Disinfection Reprocessingmentioning
confidence: 99%
“…Determining factors influencing biocides efficacy has traditionally been conducted to evaluate minimum inhibitory concentrations, or lethal effects such as European suspension test, rate-of-kill test, and in-use test that are more suitable for anti-bacterial agents [ 29 ]. Sterilisation industry relies upon 12 log 10 reductions of recalcitrant bacterial spores as biological indicators or surrogates, such as Geobacillus stearothermophilus , Bacillus atrophaeus ) for determining sterility assurance levels for different sterilants where there is significant overkill to ensure validation of processes [ 25 , 30 , 31 ]. Thus, existing disinfection processes are ultimately based upon probability of viral reduction where there is pressing need to elucidate robust real-time inactivation enumeration methods [such as 31], which is likely to be informed by predictive modelling and may create opportunities for machine learning and artificial intelligence.…”
Section: Indication Of Biocide Efficacy Against Coronavirusmentioning
confidence: 99%